American Shoemakers, 1648-1895: A Sketch of Industrial Evolution - Commons, John R. (Quarterly Journal of Economics, 1909)
Industrial stages illustrated by the shoemakers, 39. — I. The Company of Shoomakers, 1648 (Boston). Itinerant cobbler and craft gild, 40. — II. The Society of Master Cordwainers, 1789, and the Federal Society of Journeymen Cordwainers, 1794 (Philadelphia). Retailshop and wholesale-order stages, 45. — III. The United Beneficial Society of Journeymen Cordwainers, 1835 (Philadelphia). Wholesale-speculative stage, 59. Economic causes of class organization; the bargain, 65; the period of investment, 67; the level of the competitive menace, 68; protective organizations, 69. — IV. Knights of St. Crispin, 1868, 72. The factory system, 73. — V. Industrial Evolution in Europe and America. Organization and legislation for protection, 76.